Digital Transformation in Indonesian Healthcare - Ardanareswari Ayu Pitaloka; Arief Priyo Nugroho (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2021)
Digital transformation in the health sector is a necessity. The context of a pandemic has indeed accelerated these transformations but experiencing some challenges. Using surface web searching and a systematic review of google scholar data, this manuscript tries to elaborate on Indonesian healthcare digital transformation. Digital transformation in healthcare services in Indonesia has several challenges in its development. Apart from legal and ethical issues, there are social, political, and cultural contexts that make existing transformations at risk of creating conflict relations in health services. It can be concluded, the benefits of digital transformation of health services need some mitigate conflicts potential. In order to improve access and quality, its risk potential should be reduced Keywords: digital transformation, digital healthcare, health apps, risk potential.